2004
DOI: 10.1097/01.asn.0000141016.20133.33
|View full text |Cite
|
Sign up to set email alerts
|

Calcimimetic Compound Upregulates Decreased Calcium-Sensing Receptor Expression Level in Parathyroid Glands of Rats with Chronic Renal Insufficiency

Abstract: Abstract.The reduced expression level of the calcium-sensing receptor (CaR) is attributed to the hyposensitivity of parathyroid cells to extracellular calcium concentration [Ca 2ϩ ]o, which plays a crucial role in the pathogenesis of secondary hyperparathyroidism (SHPT) in patients and rats with chronic renal insufficiency (CRI). Calcimimetic compounds have been demonstrated to improve the decreased sensitivity of CaR to extracellular calcium concentration and to suppress both parathyroid hormone (PTH) ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 34 publications
5
62
0
Order By: Relevance
“…40 Although in uremia, the CaSR expression is reduced in the parathyroid gland, 41 it was not altered in the myocardium after SNX. Similar to what is seen in the parathyroid glands, 42 the CaSR expression was increased in this study after administration of the calcimimetic.…”
Section: Discussionsupporting
confidence: 73%
“…40 Although in uremia, the CaSR expression is reduced in the parathyroid gland, 41 it was not altered in the myocardium after SNX. Similar to what is seen in the parathyroid glands, 42 the CaSR expression was increased in this study after administration of the calcimimetic.…”
Section: Discussionsupporting
confidence: 73%
“…This is not, however, surprising because experimental studies have shown that CaSR signaling to suppress PTH secretion is largely preserved in vitro, even in the setting of reduced CaSR expression (32). Cinacalcet therapy has also been shown to upregulate the expressions of VDR (33) and CaSR (34), which may facilitate the inhibitory effects of vitamin D sterols and cinacalcet on PTH secretion in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The same was seen in the tubulointerstitium by immunohistochemistry. The changes in glomerular CaSR expression correspond to changes observed by others in the parathyroid glands (9,14).…”
Section: Discussionmentioning
confidence: 99%